Foot movement in impact phase of instep kicking in soccer - Shinkai, H.; Nunome, H.; Ikegami, Y.; Isokawa, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Ball impact technique is essential to produce a higher ball velocity in soccer instep kicking. However, to date only a few studies focused on foot kinematics during ball impact, in which plantar flexion motion of the foot was solely reported (Asai et al., 1995; Nunome et al., 2006). In this study, three-dimensional movement of the foot (plantar flexion / dorsal flexion, abduction / adduction, eversion / inversion) during ball impact.